2022
DOI: 10.1002/sim.9404
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical multivariate directed acyclic graph autoregressive models for spatial diseases mapping

Abstract: Disease mapping is an important statistical tool used by epidemiologists to assess geographic variation in disease rates and identify lurking environmental risk factors from spatial patterns. Such maps rely upon spatial models for regionally aggregated data, where neighboring regions tend to exhibit similar outcomes than those farther apart. We contribute to the literature on multivariate disease mapping, which deals with measurements on multiple (two or more) diseases in each region. We aim to disentangle ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Simulation studies covering a wide range of scenarios showed that DAGAR models tend to perform better than CAR models for low or moderate spatial correlation in the data, while the performances of the two classes of models are similar in the presence of strong spatial correlation. The model has subsequently been generalized to include multivariate outcomes (Gao et al, 2020, 2021).…”
Section: New Applicationsmentioning
confidence: 99%
“…Simulation studies covering a wide range of scenarios showed that DAGAR models tend to perform better than CAR models for low or moderate spatial correlation in the data, while the performances of the two classes of models are similar in the presence of strong spatial correlation. The model has subsequently been generalized to include multivariate outcomes (Gao et al, 2020, 2021).…”
Section: New Applicationsmentioning
confidence: 99%
“…As stated by the authors, the Cholesky factor has the same level of sparsity as the undirected graph ensuring scalability for analysing very large areal datasets. An extension to deal with multivariate spatial disease mapping models has been developed by Gao et al (2022). This new methodology provides reliable risk estimates with a substantial reduction in A scalable spatial modelling approach for high-dimensional areal data computational time.…”
Section: Introductionmentioning
confidence: 99%